2008
DOI: 10.1016/j.joca.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteome analysis of normal and osteoarthritic chondrocytes reveals distortion of vimentin network in osteoarthritis

Abstract: All together, this study revealed substantial alterations in the vimentin cytoskeleton in OA-affected human articular chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 41 publications
6
61
0
1
Order By: Relevance
“…In contrast, disrupting the 19 actin microfilament network resulted in comparable cell deformations between shVim-20 hMSCs and shLacZ-hMSCs ( Figure 3B). Normalized aspect ratios were still slightly 21 higher for shVim-hMSCs compared to shLacZ-hMSCs, but no longer significant at both Recently, studies have found vimentin IFs to be disrupted in chondrocytes and even in 16 MSCs harvested from osteoarthritic bone marrow 4,16,27 . Because mechanical loading is without allowing for extended culture time, as previously described 33 .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, disrupting the 19 actin microfilament network resulted in comparable cell deformations between shVim-20 hMSCs and shLacZ-hMSCs ( Figure 3B). Normalized aspect ratios were still slightly 21 higher for shVim-hMSCs compared to shLacZ-hMSCs, but no longer significant at both Recently, studies have found vimentin IFs to be disrupted in chondrocytes and even in 16 MSCs harvested from osteoarthritic bone marrow 4,16,27 . Because mechanical loading is without allowing for extended culture time, as previously described 33 .…”
mentioning
confidence: 93%
“…Mechanical properties and mechanotransduction are in 12 part regulated by the cytoskeleton, consisting primarily of actin microfilaments, 13 microtubules, and vimentin intermediate filaments (IFs) for cells of mesenchymal 14 lineage 5,7,19,23,24,29,30,34,36 . While their role in the pathogenesis of OA is still unknown, 15 vimentin IFs have recently been found to be disrupted or dispersed in osteoarthritic 16 chondrocytes 4,16 . Notably, vimentin has also been shown to be downregulated in MSCs 17 of osteoarthritic patients 27 , which raises questions about the potential efficacy of 18 autologous stem cell therapies for treatment of OA.…”
mentioning
confidence: 99%
“…The methodology developed for this investigation represents a considerable advancement on previous proteomic studies using in vitro systems to identify protein expression changes associated with cartilage pathology (6,7,20). This is the first differential proteomic analysis of cartilage-related samples using fluorescence DIGE to quantify protein expression differences.…”
Section: Discussionmentioning
confidence: 99%
“…Human chondrocyte and cartilage cultures have also been used to identify pathologic changes associated with osteoarthritis (OA), using proteomic tech-niques (6,7). However, the analysis of human tissue and synovial fluid is complicated by the genetic heterogeneity of patients, variation in disease stage, and the limited availability of well-matched control samples.…”
mentioning
confidence: 99%
“…Subsequent validation experiments clearly pointed to distortion of the vimentin organization associated with OA. In addition, novel players were identified in processes known to be involved in OA pathogenesis, such as oxidative stress, apoptosis, and metabolic activation [70]. Undoubtedly, the results generated by such differential analyses will further contribute to our knowledge of processes activated in OA-chondrocytes.…”
Section: Cartilagementioning
confidence: 94%